Left ventricular ejection fraction: clinical, pathophysiological, and technical limitations - Vancheri, Federico; Longo, Giovanni; Henein, Michael Y. (Frontiers in Cardiovascular Medicine, 2024)
Risk stratification of cardiovascular death and treatment strategies in patients with heart failure (HF), the optimal timing for valve replacement, and the selection of patients for implantable cardioverter defibrillator, are based on echocardiographic calculation of left ventricular ejection fraction (LVEF) in most guidelines. As a marker of systolic function, LVEF has important limitations being affected by loading conditions and cavity geometry, as well as image quality, thus impacting inter-and intra-observer measurement variability. LVEF is a product of shortening of the three components of myocardial fibres: longitudinal, circumferential and oblique. It is therefore a marker of global ejection performance based on cavity volume changes, rather than directly reflecting myocardial contractile function, hence may be normal even when myofibril's systolic function is impaired. Sub-endocardial longitudinal fibres are the most sensitive layer to ischemia, so when dysfunctional, the circumferential fibres may compensate for it and maintain the overall LVEF. Likewise, in patients with HF, LVEF is used to stratify subgroups, an approach that has prognostic implications but without direct relationship. HF is a dynamic disease which may worsen or improve over time according to the underlying pathology. Such dynamicity impacts LVEF and its use to guide treatment. The same applies to changes of LVEF following interventional procedures.In this review we analyze clinical, pathophysiological and technical limitation of LVEF across a wide range of cardiovascular pathologies.